Manajemen Pengembangan Sarana dan Prasarana dalam Implementasi Manajemen Berbasis Sekolah di MA Al-Falah Nagreg - M Hijrah M Saway (MANAZHIM, 2019)
Facilities and infrastructure are one of the aspect which is needed to be concerned in implementing Management Based School and the foundation is the authority and responsibility of the school. This research is the field research that was chosen by purposive. The purpose of this research is to analyze the results of research relating to planning, implementing, monitoring the problems and efforts to handle the problems in implementing the facilities and infrastructure at school. In this research, the writer uses descriptive analysis method that is started with observing, interviewing, and documenting as the steps of data collection to collect all sources that related to problems of the research. Then, the writer verifies the accurancy of the data using the technic of triangulism. After doing this research, the writer concludes that: Management based school means the changing in taking adjusments from the education center to the school. The planning of implementation the facilties and infrastructure starts with analyzing the needs, doing survey, choosing the main need and implementing educational specification, The implementation of development facilities and infrastructure is carried out through assistance of school’s comitee, students’ parents and government. The supervision of development facilities and infrastructure is done through a directly approach and non directly approach. The hading problems in implementing facilities and infrastructure is the lack of involvement of businessmen in educational environments, lack of the skills in schools; managerial comitee, lack of the competency of the students’ parents and society, and the lack of involvement of the students in the process of maintaining the facilities and infrastructure in the school. The efforts that have been done to handle this problems in implementing facilitites and infrastructure is personal coaching personnel, improving the management’s quality, developing the main commitment with the students; parents and prospective students, and also making the relation together with another school.